2020
DOI: 10.1016/j.jbusres.2020.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s consumer agency: The case of French children and recycling

Abstract: This research offers insights into children's agency in the context of recycling behaviors by exploring how children's agency might be enacted in various settings (e.g., family, school, neighborhood). Using a series of child-centered methods, the authors observe children's recycling behaviors at school and at home and investigate their behaviors using role-playing games and a verbalization phase that captures the children's understanding of recycling and their varying degrees of agency around recycling. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 48 publications
1
47
0
6
Order By: Relevance
“…It thus appears even more important to establish sustainable consumption practices and patterns as routines among that age group (Fischer et al 2017), especially as they are about to form their own households (Stanes et al 2015). Furthermore, although environmentally friendly activities among young consumers have been the focus of various studies, including the purchase of green products (Pham et al 2019), recycling (Ojala 2008;Schill et al 2020), or the use of second-hand clothing (Xu et al 2014), the anti-consumption behaviours covered in our study have largely remained unexamined to date. The behaviours originate from research on sustainable consumption (Balderjahn et al 2013) and are highly relevant for reducing the environmental impact of overconsumption (Balderjahn et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…It thus appears even more important to establish sustainable consumption practices and patterns as routines among that age group (Fischer et al 2017), especially as they are about to form their own households (Stanes et al 2015). Furthermore, although environmentally friendly activities among young consumers have been the focus of various studies, including the purchase of green products (Pham et al 2019), recycling (Ojala 2008;Schill et al 2020), or the use of second-hand clothing (Xu et al 2014), the anti-consumption behaviours covered in our study have largely remained unexamined to date. The behaviours originate from research on sustainable consumption (Balderjahn et al 2013) and are highly relevant for reducing the environmental impact of overconsumption (Balderjahn et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…It was observed that the topic of recycling in early childhood education has become popular both in Turkey and the rest of the world in recent years (e.g. Bolanos, Reeve, Reeve, Sidener, Jennings, & Ostrosky, 2020;Buil, Roger-Loppacher, & Tintoré, 2019;Kartal & Ada, 2020;Mackey, 2014;Onur, Çağlar, & Salman, 2016;Öztap & Bartan, 2019;Schill, Godefroit-Winkel & Hogg, 2020;Tosun & Demir, 2018). Mackey (2014) studied children for their understanding of the concept of recycling and emphasized that during the sustainability education process included in the program, preschool sought ways to improve their sustainability practices.…”
Section: Discussionmentioning
confidence: 99%
“…Mackey (2014) studied children for their understanding of the concept of recycling and emphasized that during the sustainability education process included in the program, preschool sought ways to improve their sustainability practices. In the study by Schill, et al, (2020), it was seen that children were knowledgeable and worried about recycling. The findings also showed that children developed their recycling abilities through self-learning and observation-based learning, often at school and sometimes in the family setting.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, changes in waste reduction and recycling depended on changes in concern about climate change. Schill et al (2020) have also shown that waste management at the household level depends on environmental concerns. Although waste management depends on climate change concerns, personal responsibility for climate change did not lead to this behaviour.…”
Section: Changes In Climate-friendly Behaviour and Its Factorsmentioning
confidence: 99%